Loyalitas Pada Wisata Heritage: Studi Kasus Pada Wisatawan Candi Prambanan - Dyah Sugandini; Esti Dwi Rahmawati; Yulia Aji Puspitasari; Yuni Istanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
This study aims to see the loyalty of tourists in the Prambanan temple in Yogyakarta as one of the Heritage tours, using respondents from foreign tourists and domestic tourists. The number of samples used in this study were 100 respondents. Data were analyzed using descriptive statistics with the SPSS program. The results of this study indicate that the loyalty of tourists as indicated by e_WOM, willingness to recommend and intention to visit again shows a high average answer. So it can be seen that tourists who visit Prambanan Temple have high loyalty to this tourist destination.